Climatic regionalization of Montenegro by applying different methods of cluster analysis - Burić, Dragan; Mihajlović, Jovan; Ducić, Vladan (Geographica Pannonica, 2023)
To carry out an "objective" regionalization of the climate of Montenegro for the period 1961–2020, this paper used cluster analysis, which is a multivariate technique that classifies a sample of subjects (objects) based on a set of variables into a single number. Based on the results (score), several groups were separated, and similar classes (groups) were grouped into the same cluster. Annual data for mean temperature and total precipitation from 18 meteorological stations were utilized. Temperature and precipitation cluster regions were separated using three different hierarchical agglomerative methods (Unweighted Pair Group Method with Arithmetic Mean (UPGMA), Single linkage, and Ward’s) and one non–hierarchical method (K–means). The Euclidean distance was used as a measure of distance for hierarchical methods, and the results were represented graphically in the form of dendrograms and thematic maps. The obtained results indicate that the singled–out temperature and precipitation cluster regions largely coincide with the established climate types in Montenegro. The cluster results further showed that the distribution of meteorological stations clearly reflects the largest part of the climatic diversity of Montenegro and indicates the spatial dimension of temperature and precipitation.